Microfluidic systems for plant root imaging - Guichard, Marjorie; Bertran Garcia de Olalla, Enric; Stanley, Claire Elizabeth; Großmann, Guido (Plant cell biology, 2020)
Plant roots adapt their development and metabolism to changing environmental conditions. In order to understand the response mechanisms of roots to the dynamic availability of water or nutrients, to biotic and abiotic stress conditions or to mechanical stimuli, microfluidic platforms have been developed that offer microscopic access and novel experimental means. Here, we describe the design, fabrication and use of microfluidic devices suitable for imaging growing Arabidopsis roots over several days under controlled perfusion. We present a detailed protocol for the use of our exemplar platform—the RootChip-8S—and offer a guide for troubleshooting, which is also largely applicable to related device designs. We further discuss considerations regarding the design of custom-made plant microdevices, the choice of suitable materials and technologies as well as the handling of the specimen.